Factors Associated with Meeting Current Recommendation for Physical Activity in Scottish Adults with Diabetes - Ahmad Salman (3173418) (2019)
It remains unclear which factors are instrumental in meeting the recommended physical activity in people with diabetes. We, therefore, aimed to determine the sociodemographic, health-related behavior and clinical factors associated with meeting the recommended levels of physical activity in Scottish adults with diabetes. The study was based on the nationally-representative cross-sectional Scottish Health Surveys (2014–2017). The study participants included a sub-sample of 1259 adults (≥16 years old) with diabetes. Physical activity was evaluated using international guidelines. Overall, 34.1% of the subjects met the recommended levels of physical activity. Independent determinants of meeting the recommended levels of physical activity include male gender (odds ratio (OR) 1.47; 95% confidence interval (CI) 1.07–2.00) and being a non-smoker (OR 1.62; 95% CI 1.02–2.56). Furthermore, meeting the recommended physical activity levels decreased with age (OR 0.96; 95% CI 0.95–0.97), having a longstanding illness (OR 0.56; 95% CI 0.34–0.93) and body mass index (OR 0.94; 95% CI 0.92–0.97), but increased with higher fruit and vegetable intake (OR 1.16; 95% CI 1.07–1.25) and mental wellbeing (OR 1.04; 95% CI 1.02–1.06). Implementation of health promotion programs that target the identified determinants is needed to improve the recommended levels of physical activity among adults with diabetes. Other Information Published in: International Journal of Environmental Research and Public Health License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ijerph16203857